The Role of Ta'zir Sanctions in Preventing Promiscuity Among Adolescents: An Islamic Criminal Law Perspective - Dava Abie Zandhika Nasution; Kharina Nur Huda; Nurhalijah Siregar; Rayhan Abyasha Az (ISNU Sumatera Utara, 2024)
Free association among adolescents has become a social issue that has attracted increasing attention due to its potential to cause various negative impacts, including deviant behavior, violations of religious norms, moral degradation, and the rise of juvenile delinquency. This phenomenon not only affects individual development but also has implications for social order and community life. From the perspective of Islamic Criminal Law, various forms of behavior leading to immoral acts, whose types and punishments are not explicitly stipulated in the Qur’an and Hadith, may be categorized as jarimah ta'zir. Ta'zir refers to a form of punishment whose determination is entrusted to the authority of the ruler or competent institution by considering the severity of the offense, public welfare (maslahah), and the objective of offender rehabilitation. This study aims to analyze the role of jarimah ta'zir in addressing free association among adolescents from the perspective of Islamic Criminal Law. The research employs a normative legal research method with conceptual and Islamic juridical approaches through an examination of the Qur’an, Hadith, scholarly opinions, and relevant literature. The findings indicate that jarimah ta'zir plays a strategic role in preventing and overcoming free association through the implementation of educational, preventive, repressive, and rehabilitative sanctions. The application of ta'zir punishment is not merely intended to create a deterrent effect but also to improve moral conduct, enhance legal awareness, and encourage adolescents to return to the values of Islamic teachings. The flexibility of ta'zir allows for the adjustment of sanctions according to social conditions and the rehabilitative needs of offenders. Therefore, the concept of jarimah ta'zir can serve as an effective instrument of Islamic law in safeguarding the morality of the younger generation and promoting public welfare. This study is expected to contribute to the development of Islamic Criminal Law studies, particularly regarding efforts to address free association among adolescents.